Correlation in biological literacy and critical thinking skills of science students through problem-based learning model integrated by macromedia flash - Anindita SHM Kusuma (Jurnal Pijar Mipa, 2023)
Biological literacy and critical thinking skills are two abilities students studying biology must possess. This study aimed to determine the correlation between biological literacy skills and critical thinking skills of class XI Science at Senior High School 1 Aikmel Through the Problem-Based Learning model integrated by Macromedia Flash. The research method is correlational research. The sample in this research were students of class XI Science 1 and XI Science 3 at Senior High School I Aikmel. The data analysis used in this study is a simple linear regression analysis. The results showed a relationship between biological literacy skills and critical thinking skills of class XI Science at Senior High School 1 Aikmel Through the Problem-Based Learning model integrated by Macromedia Flash. The value of the correlation coefficient (r) of biological literacy with critical thinking skills is 0.712 (high). The direct relationship between biological literacy and critical thinking skills is positive. The coefficient of determination (r2) is 50.8%. The regression line equation for the relationship between biological literacy and students' critical thinking skills in learning using the Problem-Based Learning model with Macromedia Flash is Y =43.847+0.568X.